THE ROLE OF DIET IN THE DEVELOPMENT OF ACNE VULGARIS: A REVIEW OF THE LITERATURE - Wiktoria Auguścik; Katarzyna Bielawska; Aleksandra Tlak (International Journal of Innovative Technologies in Social Science, 2025)
Background: Acne vulgaris is a chronic inflammatory skin disorder influenced by genetic, hormonal and environmental factors. In recent years, the role of diet in acne development and severity has received increasing attention. Objective: The aim of this review was to summarise and evaluate the current evidence regarding the association between dietary patterns and acne vulgaris. The review focused on key nutritional factors, such as the glycemic index, dairy products, omega-3 fatty acids, probiotics and micronutrients. Methods: A literature search was conducted using the databases PubMed, Scopus, Web of Science and Google Scholar to identify studies published between 2010 and 2025. Twenty-six peer-reviewed articles, including clinical trials, observational studies and reviews, were included in the analysis. The data were synthesised qualitatively based on dietary categories and reported acne outcomes. Results: Diets with a high glycemic load, dairy consumption and whey protein supplementation were associated with acne prevalence and severity. By contrast, omega-3 fatty acids, adherence to the Mediterranean diet and probiotic supplementation demonstrated anti-inflammatory and protective effects. Micronutrients such as vitamins A, D and E, as well as zinc, also contributed to improved skin health and reduced lesion counts. However, despite these consistent trends, the heterogeneity of study design and dietary assessment limited the possibility of making direct comparisons between studies. Conclusion: Diet plays a significant role in modulating acne vulgaris. Low-glycaemic, anti-inflammatory and nutrient-rich diets may complement conventional acne therapies. Further randomised controlled trials are needed to confirm causal relationships and establish evidence-based dietary recommendations for managing acne.